TINGKAT EFISIENSI PEMASARAN DAY OLD DUCK (DOD) DI DESA MODOPURO KABUPATEN MOJOKERTO - Vivi Irawati; Sri Widayanti; Wahyu Santoso (Program Studi Agribisnis, Fakultas Pertanian, 2021)
The development of Day Old Duck (DOD) marketing activities in Modopuro Village, Mojokerto Regency can be done by selecting the most efficient marketing channel. The purpose of this study is to measure the level of marketing efficiency of DOD. The marketing efficiency indicator itself can be seen based on the marketing channel, the amount of margin and the value of the farmer's share, while to strengthen the measurement of the level of marketing efficiency, it is analyzed using the marketing efficiency index method. The results showed that there were four DOD marketing channels in Modopuro Village, namely channel I: hatchers - collectors - consumers, channel II: hatchers - consumers, channel III: hatchers - retailers - consumers, channel IV: hatchers - collectors - retailers - consumer. In succession, the marketing margins for the four channels are IDR 4,500 / head, IDR - / head, IDR 1,500 / head, and IDR 5,500 / head. The farmers' share value for channel I was 61%, channel II was 100%, channel III was 80%, and channel four was 53%. As for the analysis of the marketing efficiency index, the value of ME in the four DOD marketing channels, respectively, is 26, 31, 27, and 15.